2009
DOI: 10.1111/j.1651-2227.2009.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of bronchiolitis without antibiotics: a multicentre randomized control trial in Bangladesh

Abstract: In hospital settings, managing bronchiolitis with only supportive measures but without antibiotics remains preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 19 publications
0
40
0
1
Order By: Relevance
“…10 Kabir et al showed that most of the children were within 2-12 months of age (71.5%). 5 Bradley et al found age as a significant factor in severity of infection; the younger the infant, the more severe the infection. 11 Sex distribution of the patients (male:female; 1.9:1) was almost similar to the study of Bashar et al who found male to female ratio 1.8:1 whereas Kabir et al showed male:female ratio 2.7:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Kabir et al showed that most of the children were within 2-12 months of age (71.5%). 5 Bradley et al found age as a significant factor in severity of infection; the younger the infant, the more severe the infection. 11 Sex distribution of the patients (male:female; 1.9:1) was almost similar to the study of Bashar et al who found male to female ratio 1.8:1 whereas Kabir et al showed male:female ratio 2.7:1.…”
Section: Discussionmentioning
confidence: 99%
“…3 Risk factors implicated in the development of severe bronchiolitis include young age, male sex, parental smoking, low socioeconomic background, using of wood burning stoves, and non-breastfeeding child. 1,4,5 Environmental tobacco smoke (ETS) is an important and established risk factor for both susceptibility and severity of bronchiolitis. 6 Currently, there are 1.3 billion smokers in the world.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that poor nutrition is one of the causes of microcephaly 16 . In this study under nutrition and wasting is more prevalent in pneumonia group and consistently microcephaly is also significantly more in pneumonia group in comparison to bronchiolitis group (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Macrolides are thought to have anti-inflammatory activities as well as antibiotic activity (Culic et al, 2001), and so are thought to have potential benefit for treating bronchiolitis. Of the five studies included in the review, one smaller study including 21 children found that clarithromycin treatment may reduce hospital admission (8% clarithromycin versus 44% placebo, P = 0.081), but this study was associated with a potential higher risk of performance, detection and reporting bias (Kabir et al, 2009). One other study found mixed results for the effects of antibiotics on wheeze, but did not identify any difference for other symptom measures (Mazumder et al, 2009).…”
Section: Antibioticsmentioning
confidence: 99%
“…One other study found mixed results for the effects of antibiotics on wheeze, but did not identify any difference for other symptom measures (Mazumder et al, 2009). Four included studies did not find any difference between antibiotics and placebo for their primary outcomes of length of illness (Field et al, 1966) or lengt of hospital stay (Kabir et al, 2009;Kneyber et al, 2008;Mazumder et al, 2009). Despite these results, antibiotics are commonly used in 34% to 99% of hospitalized infants, even in those that do not require mechanical ventilation (Kabir et al, 2003;Vogel et al, 2003).…”
Section: Antibioticsmentioning
confidence: 99%